Future district heating systems and technologies: On the role of smart energy systems and 4th generation district heating. (15th December 2018) - Lund, Henrik; Duic, Neven; Østergaard, Poul Alberg; Mathiesen, Brian Vad
Abstract: This paper provides a perspective on the development of future district heating systems and technologies and their role in future smart energy systems. The reviewed papers elaborate on or otherwise contribute to the theoretical scientific understanding of how we can design and implement a suitable and least-cost transformation into a sustainable energy future. Focus is on the important role of the next generation of district heating and cooling technologies. The status of the scientific contributions demonstrates a high level of understanding of how to deal with the technical aspects. The primary current challenge seems to be the understanding of the implementation of these. Highlights: A transformation into low-temperature becomes essential for future district heating. High level of understanding of how to deal with the technical aspects. Primary current challenge seems to be the understanding of the implementation.